System For Preparing Professors And Teachers For Pedagogical Management Of Students' Academic Activities In Higher Education Institutions - Avazov Azam Januzaqovich (Genius Journals, 2023)
In this article, the activities of pedagogical management of students' educational activities in the system of retraining and professional development of professors and teachers are studied.
Keywords: Vocational Training; Training System; Spiral Of Knowledge